INTERNAL AUDIT IN COVID-19 ENVIRONMENT: KEY ASPECTS AND PERSPECTIVES OF REMOTE AUDITING - Kljajić, Maja; Mizdraković, Vule; Hadrović Zekić, Blaženka (The European Journal of Applied Economics, 2022)
It was very difficult to predict global pandemic caused by the new coronavirus COVID-19 disease that flared up around the world. There is no doubt that the pandemic will have serious consequences on worldwide economy because besides being a health crisis, pandemic threatens to become economic and financial crisis. Therefore, management of service providing entities were left in dilemma choosing a model of performing business activities, and taking care of the health of employees, at the same time. This paper discusses possible solutions related to the internal audit, as a service providing profession. Findings from the authors in the field lead to the conclusion that auditors could use this business environment as an opportunity for complete digital transformation, and extensive use of remote auditing, since the function of internal audit can be further improved by using new information and communication technologies. Results of a research focused on the opinions of certified internal auditors from the Republic of Serbia showed that benefits of remote auditing in internal audit are prevailing over disadvantages. Quality level of performed audits increased or stayed the same, as well as the level of trust of audit client management, while decrease of travel-related costs and time savings are considerable.
Keywords: remote auditing; pandemic; internal auditor; digital transformation; ICT